2005
DOI: 10.1063/1.2130529
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature emission at 1.6μm from InGaAs quantum dots capped with GaAsSb

Abstract: Room temperature photoluminescence at 1.6μm is demonstrated from InGaAs quantum dots capped with an 8nm GaAsSb quantum well. Results obtained from various sample structures are compared, including samples capped with GaAs. The observed redshift in GaAsSb capped samples is attributed to a type II band alignment and to a beneficial modification of growth kinetics during capping due to the presence of Sb. The sample structure is discussed on the basis of transmission electron microscopy results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(89 citation statements)
references
References 12 publications
1
88
0
Order By: Relevance
“…39 In fact the observed heights of the QDs are as much as twice compared with QDs capped with pure GaAs. Ripalda et al 40 reported the use of GaAsSb capping to extend the emission wavelength of InGaAs quantum dot structures and observed that a type II alignment takes place when the Sb content of the capping layer is higher than 14%. Furthermore they also report an order of magnitude improvement of the room-temperature luminescence intensity in the 1.3 m spectral range for GaAsSb covered InAs QDs due to increased hole localization.…”
Section: Role Of Segregation In Inas/gaas Quantum Dot Structures Cappmentioning
confidence: 99%
“…39 In fact the observed heights of the QDs are as much as twice compared with QDs capped with pure GaAs. Ripalda et al 40 reported the use of GaAsSb capping to extend the emission wavelength of InGaAs quantum dot structures and observed that a type II alignment takes place when the Sb content of the capping layer is higher than 14%. Furthermore they also report an order of magnitude improvement of the room-temperature luminescence intensity in the 1.3 m spectral range for GaAsSb covered InAs QDs due to increased hole localization.…”
Section: Role Of Segregation In Inas/gaas Quantum Dot Structures Cappmentioning
confidence: 99%
“…The strong red shift observed by using GaAsSb instead of GaAs capping layers has been attributed to a type II band alignment [64,70]. However, the structural properties of these QDs have not been studied, despite the fact that they could be significantly different from those of GaAs-capped QDs.…”
Section: Gaassb Capping Of Inas/gaas Qdsmentioning
confidence: 99%
“…In the last few years, GaAsSb capping layers have also been used to increase the emission wavelength of InAs/GaAs QDs [63,69] and room temperature photoluminescence at 1.6\xm has recently been reported from GaAsSb-capped In(Ga)As/GaAs QDs [64,70]. The strong red shift observed by using GaAsSb instead of GaAs capping layers has been attributed to a type II band alignment [64,70].…”
Section: Gaassb Capping Of Inas/gaas Qdsmentioning
confidence: 99%
See 1 more Smart Citation
“…This capping layer leads to QD emission at 1.62 μm at RT. 12 This redshift was related with a type-I to type-II transition of the system energy levels with the hole deeply confined in the QD and the electron wave function delocalized in the capping quantum well (QW). Liu et al have quantified the concentration of Sb that leads to such type-I to type-II transitions-14%-in similar structures capped with a GaAs 1−x Sb x QW.…”
Section: Introductionmentioning
confidence: 99%